Real mom real journey / Elvina Lim Kusumo; penyunting, Noni Rosliyani, Ranny Affandi; ilustrasi, Anisa Meilasyari - ELVINA LIM KUSUMO; NONI ROSLIYANI; RANNY AFFANDI; ANITA MEILASYARI (B First, 2016)
196 hlm. : ilus. ; 21 cm.